Utilization of goat milk for the preparation of paneer - kannan, radha; Kanjirathummoottilsalu, viji; Raja kumar, nagesh (Indian Journal of Dairy Science, 2017)
An attempt was made to utilize goat milk for the preparation of paneer in combination with buffalo milk. In this experiment, paneer was prepared by the admixture of goat and buffalo milk at different proportions. Paneer prepared from 100 percent buffalo milk was used as control. Goat milk was incorporated at 25 percent (T1), 50 percent (T2) and 75 per cent (T3) levels with buffalo milk for the preparation of paneer. Chemical qualities of the prepared paneer samples at refrigerated as well as at room temperature storage were assessed. Freshly prepared paneer was creamy white in colour and had no goaty smell and salty taste. During refrigerated storage, there was no significant change in fat and moisture content of paneer. Fat percentages of paneer in all the treatment groups were significantly higher than (P< 0.01) control. The moisture content of T1 paneer was significantly (P